The law and economics of antitrust and intellectual property : an Austrian approach - Kallay, Dina, 1972- (Cheltenham, UK ; Northampton, MA, USA : E. Elgar, 2004)
This book provides a theoretical appraisal of the complex issues that arise when antitrust and IP considerations seem to be at odds with one another. It offers an alternative to the Chicago school of antitrust, and makes a contribution to the Austrian school of economics. Lawyers, industrial economists and academics working on IP, antitrust and competition will all find this to be an informative volume. It will also be a source of reference for anyone interested in philosophy of property rights.
Includes bibliographical references (p. 210-238) and index.
oif 11/02/15
Loan
Keywords: Antitrust law -- Austria; Intellectual property -- Economic aspects; Intellectual property -- Austria